Digital Entrepreneurship and Business Innovation: Strategies for Indonesian SMEs in the Era of Industry 4.0 - Nengsi Sudirman; Nurfaisah (Journal of Indonesian Scholars for Social Research, 2025)
The rapid advancement of Industry 4.0 has significantly transformed the entrepreneurial landscape, particularly for small and medium-sized enterprises (SMEs) in Indonesia. Digital entrepreneurship has emerged as a critical driver of business innovation, enabling SMEs to enhance operational efficiency, expand market reach, and develop competitive advantages. This study explores the role of digital entrepreneurship in fostering business innovation, focusing on strategies that Indonesian SMEs adopt to navigate the digital economy. By utilizing a qualitative research approach, this paper examines case studies of SMEs that have successfully integrated digital technologies, such as e-commerce platforms, cloud computing, artificial intelligence, and blockchain, into their business models. The findings reveal that digital transformation enhances SMEs’ adaptability, productivity, and customer engagement. Key success factors include digital literacy, strategic use of online marketplaces, and the adoption of automation tools to streamline operations. However, SMEs also face significant challenges, including digital infrastructure limitations, cybersecurity risks, financial constraints, and resistance to technological change. The study highlights the importance of government policies, financial incentives, and digital training programs in supporting SMEs’ digital transition. This paper argues that a comprehensive and collaborative approach—where businesses, policymakers, and technology providers work together—is essential for maximizing the potential of digital entrepreneurship in Indonesia. By embracing digital transformation, SMEs can drive innovation, strengthen economic resilience, and contribute to sustainable economic growth in the digital era.